PELAKSANAAN PEMBELAJARAN PENJASKES SECARA DARING KELAS X.I A.1 SMA NEGERI 3 PEKANBARU PADA MASA COVID 19 - Hasbi Ansori Umaya; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstrack: The implementation of learning during the Covid-19 pandemic has beendetermined in accordance with government regulations to limit the spread of the Covid-19 virus,which is to conduct online learning. The aim of this study was to find out how online physicaleducation can be applied during the Covid-19 pandemic. This research uses descriptivequantitative research methods. The instrument used in this study was in the form of aquestionnaire that was distributed to the sample, namely Class XI A1 SMA Negeri 3 Pekanbaruout of a total of 24. A purposeful technique was used in the selection of the study sample becausethe selected sample found a correlation during the learning activities at State Senior High School3 Pekanbaru. The validity of the instrument with the value validity and reliability in this study is0.954. The results of the study show that the implementation of physical education learning fromstudent data falls into the very good category, this is proven by the learning media when onlinelearning plays quite an important role as teacher communication in conveying material tostudents. The role of the teacher in the implementation of online physical education is very good,as can be seen in the learning process according to the curriculum method. Furthermore, fromthe research results, the role of the director falls in the category of very good by facilitatingteachers in the online learning of physical education. The results of the study are expected tobecome a reference for the implementation of online physical education, so that the resultsobtained are maximumKeywords: Online Learning, Physical Education, Covid-19